Arabidopsis SIZ1 positively regulates alternative respiratory bypass pathways - Bong Soo Park1, Sung-Il Kim1, Jong Tae Song2 & Hak Soo Seo1,3,* (BMB Reports, 2012)
Plant mitochondria possess alternative respiratory pathwaysmediated by the type II NAD(P)H dehydrogenases and alternativeoxidases. Here, E3 SUMO ligase was shown to regulatealternative respiratory pathways and to participate in the maintenanceof carbon and nitrogen balance in Arabidopsis. Thetranscript abundance of the type II NAD(P)H dehydrogenasesNDA2 and NDB2 and alternative oxidases AOX1a and AOX1dgenes was low in siz1-2 mutants compared to that in wild-type.The addition of nitrate or ammonium resulted in a decrease oran increase in the expression of the same gene families, respectively,in both wild-type and siz1-2 mutants. The amountof free sugar (glucose, fructose and sucrose) was lower in siz1-2mutants than that in wild-type. These results indicate that lownitrate reductase activity due to the AtSIZ1 mutation is correlatedwith an overall decrease in alternative respiration andwith a low carbohydrate content to maintain the carbon to nitrogenratio in siz1-2 mutants.